VD_FINDINFO AVS 20/22 - 3/2023 vom 14. März 2023 - VD Tribunal cantonal (2023)
COTISATION AVS/AI/APG, MÉNAGE COMMUN, DROIT D'ÊTRE ENTENDU, CONTINGENT, MAXIMUM | 29 al. 2 Cst., 35 LAVS, 25 al. 1 LPGA, 25 al. 2 LPGA